Assessing factors in considering ergonomics at construction project – an overview / Farrah Rina Mohd Roshdi ... [et al.] - Mohd Roshdi, Farrah Rina; Saharuddin, Shafikah; Mohamed Yusof, Nur Fatiha; Mohd Noor, Siti Nur Aishah (2021)
Construction activities in Malaysia are industries that interact with humans with technological support and tools in performing various tasks given to a large environment. However, these construction activities are among the sectors that are exposed to high risks of accidents and injuries. An organization must be vigilant in knowledge and procedures involving the management of Occupational Safety and Health (OSH). This will indirectly affect the life cycle of its project. Therefore, this research is conducted for the purpose of identifying Human Factors associated with Ergonomics (HF/E) to increase safety and professional satisfaction in terms of comfort and convenience in the workplace. Based on the literature, there are five (5) factors in HF/E consideration. Starting from human interaction to health and safety, environment, design of equipment and work task, workplace and work process. While there are economic factors that drive continuous HF/E principle and improvement in the workplace, organizational management should have an appropriate investment in HF/E prior to on-site implementation is a good economy for organizations towards human well-being and happiness among society. The noble intention of management by placing people as a priority, positive reflection on the organization is a timely project, cost-saving with a profitable project and the quality shown by the controlled OSH itself is being pursued. This is a valuable investment at the early stages of the project with a high emphasis on safety and human performance on project costs.